Acute exposure to a commercial formulation of Azoxystrobin alters antioxidant enzymes and elicit damage in the aquatic macrophyte Myriophyllum quitense - Garanzini, Daniela Soledad (2019)
Azoxystrobin is a strobilurin of growing concern in aquatic environments because it is the most sold fungicide worldwide, however, the information available about its effect on aquatic non-target organisms is scarce. The objective of the present study was to evaluate potential physiological, biochemical, and genetic effects at environmentally relevant (1–10 μg/L) and elevated (100–500 μg/L) concentrations in the aquatic macrophyte Myriophyllum quitense exposed to the commercial formulation AMISTAR ® . Following an acute 24-h exposure, there were no effects of AMISTAR ® on photosynthetic pigments at any of the concentrations evaluated. Glutathione-S-transferase activity was significantly elevated at 1 and 10 μg/L AZX. Significant decrease of catalase and guaiacol peroxidase activities in plants exposed to 500 μg/L, and to 100 and 500 μg/L, respectively, and an increase in glycolate oxidase activity at 500 μg/L was observed. DNA damage at 100 and 500 μg/L was observed. These data indicate that although environmentally relevant levels of AMISTAR ® did not result cytotoxic, this fungicide was genotoxic, affecting the physiological process of photorespiration and caused oxidative damage at high concentrations. In this sense, it is necessary to explore sub-lethal responses in non-target organisms because some effects could promote further potential long-term biological consequences in a context of repeated pulses of exposure.